HUBUNGAN SHOLAT DENGAN HASIL BELAJAR PESERTA DIDIK - Linda Juliharti; Firman Firman (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
Student learning outcomes are one of the spearheads of an education. If the learning outcomes of students are good, then an educational process will succeed. But the reality seen lately is the decline in student learning outcomes. The purpose of this study was to find out what causes the learning outcomes of students to decrease and whether there is a connection between prayers performed by students can improve student learning outcomes. This research departs from Allah's words contained in the Koran that if you want to be smart and successful, then carry out the rules and commands of Allah SWT, one of which is by praying. Prayer can prevent evil and evil deeds, and prayer can make a person rich and successful. And it does not rule out the possibility of being able to make someone smart so that the learning outcomes are good. This research method is a survey and field study with data collection techniques is by observation and questionnaire. The results obtained are that there is a very significant relationship between students' prayer observance and student learning outcomes. Students who are religious and disciplined in praying five times a day have a strong influence on their learning outcomes. Not only learning outcomes, the morals of these students also have good morals when compared to students who do not or rarely pray.